Autorrealização no trabalho, obstáculos e possibilidades na visão de executivos brasileiros e sua interface com o processo de individuação - Lucas Júnior, Adilson Rodrigues (2019)
This research seeks to understand the comprehension of self-actualization at work, its obstacles and instruments implied in the process of its construction and the existing interface between the theories of “self-actualization” from Abraham Maslow and “individuation” from Carl Gustav Jung. It was used the Q Methodology in 12 participants, executives of large Brazilian companies, aged between 40 and 55 years. The theoretical basis is based on the study of the processes of "individuation" of Jung and "self-realization" of Maslow. The study was carried out considering the field of work as a backdrop, thus seeking to understand the view of executives in the current scenario of globalization, high competitiveness, technology and constant changes. The results emphasize and point out three needs or requirements to achieve self-actualization: autonomy, adaptability and the Self-other relationship. The research showed us that without autonomy to decide and act through their beliefs there is no self-actualization, in the current world, where the change is the great constant, the adaptability is mandatory. The Self-Other relation pointed out different characteristics or stages of self-actualization, through divergence and ways of dealing with the other